Life cycle assessment of tailings management options: a conceptual case study in Western Australia - Carneiro, A; Fourie, AB (Mine Closure 2019: Proceedings of the 13th International Conference on Mine Closure, 2019)
The vast amount of waste produced by the mining industry, of which a large proportion is tailings, has the potential to cause numerous environmental problems, and represents a possible barrier to sustainability. Although the choice of a strategy for tailings management has historically been dictated primarily by technical and economic factors, the sustainability of the selected tailings disposal method is becoming increasingly important in decision-making. Life cycle assessment (LCA) has been widely adopted as an environmental systems analysis tool and can be used for evaluating the environmental impacts of mining and mineral processing operations from a life cycle perspective. In spite of its appeal, however, the application of LCA in the mining industry, especially in tailings management is still a work in progress. Aimed at addressing this research gap, this paper reports on the results of a cradle-to-grave LCA study carried out to investigate the environmental profile of two different tailings management options. A conceptual case study for the disposal of gold tailings in Western Australia as a slurry, or as filtered tailings, was considered. The environmental impacts of each option were assessed, environmental hotspots were identified, and cleaner production measures were suggested to improve the overall environmental performance of tailings operations in Australia. In the context of mine waste management, this paper ends with a discussion addressing the benefits and challenges of applying LCA as an environmental decision-support tool, providing more information to the decision-making process and facilitating better communication with stakeholders.
Keywords: tailings management